A Study on Practices of Tour Operators and Development of Sustainable Tourism in Tamil Nadu - D, Balaji; T, Milton (International Journal of Psychosocial Rehabilitation, 2020)
Tour operators are playing crucial role in developing sustainable tourism by adopting various sustainable tourism management practices and using their experiences very sensibly. The results show that the domestic tourists are agreed with tour operators minimize use of resources for operations, tour operators give highest economic gains to local communities, tour operators adopt sustainability principles for tourism activities, tour operators reduce harmful impacts on environment, tour operators use local suppliers on the basis of sustainable practices, tour operators offer fresh and local foods, tour operators provide opportunities to shop local arts and crafts products and tour operators showcase local culture and social values. Significant difference is there between practices of tour operators for development of sustainable tourism and personal features of domestic tourists. Level of sustainable tourism development is positively, significantly and moderately related with practices of tour operators for development of sustainable tourism. Thus, tour operators should provide larger social benefits to local communities and they must give local accommodations to tourists. Further, tour operators should encourage environment responsible behaviour of tourists and they must be harmonious with production and consumption activities and nature.